2018
DOI: 10.2196/jmir.9666
|View full text |Cite
|
Sign up to set email alerts
|

Theory-Based Digital Interventions to Improve Asthma Self-Management Outcomes: Systematic Review

Abstract: BackgroundAsthma is a chronic disease requiring effective self-management to control it and prevent mortality. The use of theory-informed digital interventions promoting asthma self-management is increasing. However, there is limited knowledge concerning how and to what extent psychological theory has been applied to the development of digital interventions, or how using theory impacts outcomes.ObjectiveThe study aimed to examine the use and application of theory in the development of digital interventions to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 64 publications
1
35
0
1
Order By: Relevance
“…The findings demonstrated the benefits of an intervention program guided by the self-efficacy model on the health outcomes for patients with chronic diseases [ 35 ]. The results are consistent with a systematic review recommending of using all self-efficacy strategies to optimise the effectiveness of self-management programs for chronic diseases such as asthma [ 10 ]. This study was based on Bandura's self-efficacy model through performance accomplishment, vicarious experience, verbal persuasion, and self-evaluation of physiological and emotional states [ 11 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The findings demonstrated the benefits of an intervention program guided by the self-efficacy model on the health outcomes for patients with chronic diseases [ 35 ]. The results are consistent with a systematic review recommending of using all self-efficacy strategies to optimise the effectiveness of self-management programs for chronic diseases such as asthma [ 10 ]. This study was based on Bandura's self-efficacy model through performance accomplishment, vicarious experience, verbal persuasion, and self-evaluation of physiological and emotional states [ 11 ].…”
Section: Discussionsupporting
confidence: 87%
“…Evidence showed that self-management programs guided by a theoretical framework provide solid basis and lead to effective outcomes [ 10 ]. Bandura's self-efficacy model includes efficacy-expectation (performance accomplishment, vicarious experience, verbal persuasion, and physiological information) and outcome-expectation (what outcome people expect from engaging in a particular behaviour) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the specific learning methods are generally clear, the reasoning behind them and adaptation to specific user groups do not become evident from WTPs’ sections, such as About this course or Aims and objectives . That this is an important shortcoming is shown by previous findings that indicate the effectiveness of asthma self-management interventions with a strong theoretical framework [36]. Apart from an WTP’s theoretical and methodological approaches, its disease-specific contents need to cover all or at least the most relevant and right issues, evident from latest research, medical guidelines, and expert reviews, to be of high quality.…”
Section: Discussionmentioning
confidence: 99%
“…A large, and growing, number of digital technologies have been developed to help support the care and self-management of people with asthma [7][8][9]. Previous systematic reviews have found that digital interventions can help support asthma health management, particularly by improving medication adherence [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This is not to be confused with information sources (see first footnote). ‡ The frameworks by Arksey and O'Malley (6) and Levac and colleagues (7) and the JBI guidance (4, 5) refer to the process of data extraction in a scoping review as data charting. § The process of systematically examining research evidence to assess its validity, results, and relevance before using it to inform a decision.…”
mentioning
confidence: 99%